Coated platelets function in platelet-dependent fibrin formation via integrin αIIbβ3 and transglutaminase factor XIII - Nadine J.A. Mattheij; Frauke Swieringa; Tom G. Mastenbroek; Michelle A. Berny-Lang; Frauke May; Constance C.F.M.J. Baaten; Paola E.J. van der Meijden; Yvonne M.C. Henskens; Erik A.M. Beckers; Dennis P.L. Suylen; Marc W. Nolte; Tilman M. Hackeng; et al. (Haematologica, 2016)
Coated platelets, formed by collagen and thrombin activation, have been characterized in different ways: i) by the formation of a protein coat of α-granular proteins; ii) by exposure of procoagulant phosphatidylserine; or iii) by high fibrinogen binding. Yet, their functional role has remained unclear. Here we used a novel transglutaminase probe, Rhod-A14, to identify a subpopulation of platelets with a cross-linked protein coat, and compared this with other platelet subpopulations using a panel of functional assays. Platelet stimulation with convulxin/thrombin resulted in initial integrin αIIbβ3 activation, the appearance of a platelet population with high fibrinogen binding, (independently of active integrins, but dependent on the presence of thrombin) followed by phosphatidylserine exposure and binding of coagulation factors Va and Xa. A subpopulation of phosphatidylserine-exposing platelets bound Rhod-A14 both in suspension and in thrombi generated on a collagen surface. In suspension, high fibrinogen and Rhod-A14 binding were antagonized by combined inhibition of transglutaminase activity and integrin αIIbβ3. Markedly, in thrombi from mice deficient in transglutaminase factor XIII, platelet-driven fibrin formation and Rhod-A14 binding were abolished by blockage of integrin αIIbβ3. Vice versa, star-like fibrin formation from platelets of a patient with deficiency in αIIbβ3 (Glanzmann thrombasthenia) was abolished upon blockage of transglutaminase activity. We conclude that coated platelets, with initial αIIbβ3 activation and high fibrinogen binding, form a subpopulation of phosphatidylserine-exposing platelets, and function in platelet-dependent star-like fibrin fiber formation via transglutaminase factor XIII and integrin αIIbβ3.